Usually the independence of eigenvalues are shown for matrices, I did a proof without considering matrices.
Let $T:V\to V$ be a linear operator and let $X=${$v_1,v_2,...,v_m$} be eigenvectors each corresponding to a different eigenvalue then $X$ is linearly independent.
Proof: Suppose this is wrong and $X$ is linearly dependent. Then there are atleast two of which (if there were only one, that would make an eigenvector to be $0$) are nonzero $a_i \in F$ such that: $$ a_1v_1+a_2v_2+⋯+a_mv_m=0 \tag{*} $$
Let us pick only the vectors whose coefficients are nonzero and write:
$$α_1 u_1+α_2 u_2+⋯+α_k u_k=0$$ where for each $i$, $u_i=v_j$ for some $j$. (We don't pick the same vector twice here). Now all $\alpha$'s are different than $0$ in this context. Now let us multiply each side of this equation with $a_1^{-1}$ (since $a_1\neq 0$, $a_1^{-1}\in F$) to get:
$$ u_1+α_1^{-1}α_2u_2+⋯+α_1^{-1}α_ku_k=0 \tag{**} $$
Since each $u_i$ is an eigenvector we may write $Tu_i=\lambda_iu_i$ and we apply $T$ to the both sides of this equation to get:
$$\lambda_1u_1+\lambda_2α_1^{-1}α_2u_2+⋯+\lambda_kα_1^{-1}α_ku_k=0$$ and since $\lambda_1 \neq 0$ we can multiply each side with $\lambda_1^{-1}$ to get:
$$u_1+λ_1^{-1} λ_2 α_1^{-1} α_2 u_2+⋯+λ_1^{-1} λ_k.α^{-1} α_k u_k=0$$
From this equation and the $(**)$ equation we get:
$$ α_1^{-1} α_2 u_2+⋯+α_1^{-1} α_k u_k=λ_1^{-1} λ_2 α_1^{-1} α_2 u_2+⋯+λ_1^{-1} λ_k.α_1^{-1} α_k u_k$$
and this equation can be multiplied by $\alpha_1$ to get:
$$ α_2 u_2+⋯+α_k u_k=λ_1^{-1} λ_2 α_2 u_2+⋯+λ_1^{-1} λ_k.α_1^{-1} α_k u_k $$ which is $$ (1-λ_1^{-1} λ_2 ) α_2 u_2+⋯+(1-λ_1^{-1} λ_k ) α_k u_k=0 $$ since all the $a_i$ are nonzero, none of these coefficients can be $0$, had it been the case we would have for some $i\neq 1$,$1-λ_1^{-1} λ_i=0$ which is $λ_1=λ_i$ and this can't be since we picked $\lambda$'s to be distinct eigenvalues. Now if we rename each coefficient as $(1-λ_1^{-1} λ_2 ) α_2=β_2$, $(1-λ_1^{-1} λ_3 ) α_3=β_3$, $\ldots$, $(1-λ_1^{-1} λ_k ) α_k=β_k$ we get:
$$ β_2 u_2+β_3 u_3+⋯+β_k u_k=0 $$ where all $\beta_i$ are nonzero. This is precisely the same case within the equation $(*)$ (except we have $k-1$ vectors now) so we may apply the same procedure to this equation to get:
$$ (1-λ_2^{-1} λ_3 ) β_3 u_3+⋯+(1-λ_2^{-1} λ_k ) β_k u_k=0 $$ and for the same reasoning each coefficient is nonzero and we rename coefficients once more as $$γ_3=(1-λ_2^{-1} λ_3 ) β_3$$ and so on to get another equation but this time without $u_1$ and $u_2$. Since we have finite vectors, we keep doing this process, after $(k-1)$th iteration we get the equation:
$$ (1-λ_{k-1}^{-1} λ_k ) A_k u_k=0 $$
and since $A_k \neq 0$ (due to the process) and $u_k \neq 0$ we must have $$ 1-λ_{k-1}^{-1} λ_k=0 $$
which leads to the contradiction $λ_{k-1}=λ_{k}$.
What do you think about this proof? Is it valid?